Ayurveda Body–Mind Constitutional Types and Role of Yoga Intervention Among Type 2 Diabetes Mellitus Population of Chandigarh and Panchkula Regions. Issue 3 (July 2020) - Sivapuram, Madhava Sai; Srivastava, Vinod; Kaur, Navneet; Anand, Akshay; Nagarathna, Raghuram; Patil, Suchitra; Biman, Saranga; Chander, Ishwar; Jyoti, Saras; Nagendra, Hongasandra Ramarao
Background: Type 2 diabetes needs a better understanding of etiological factors and management strategies based on lifestyle and constitutional factors, given its high association rate with many cardiovascular, neurological disorders, and COVID-19 infection. Purpose: The present study was undertaken to investigate the effect of Diabetes-specific integrated Yoga lifestyle Protocol (DYP) on glycemic control and lipid profiles of diabetic adults. Along with the DYP intervention, the individuals residing in Chandigarh and Panchkula union territories in the northern part of India were assessed for Ayurveda-based body–mind constitutional type. Ayurveda describes body–mind constitution as " prakriti, " which has been discussed from two angles, namely physiological and psychological as body and mind are correlated. Methods: Cluster sampling of waitlist control study subjects was used as the sampling method for the study. A total of 1, 215 registered subjects (81 diabetic) responded in randomly selected clusters in Chandigarh and Panchkula. Ayurveda physicians did Ayurveda body–mind constitutional assessment called prakriti assessment (physiological body–mind constitution assessment) in 35 participants (23 diabetic, 12 prediabetic) as a part of the study. Results: A group of 50 subjects was randomly selected for yoga intervention out of 81 diabetes mellitus adults, and 31 subjects were enrolled as waitlist controls. A significant decrease in the glycosylated hemoglobin levels from 8.49 ± 1.94% to 7.97 ± 2.20% in the intervention group was noticed. The lipid profiles of the DYP intervention and control groups were monitored. Three-month follow-up results of lipid profile diagnostic tests in intervention and control groups showed a significant difference between the two groups ( P < 0.05). Most diabetic and prediabetic individuals were found to have pitta dosha ( pitta controls all heat, metabolism, and transformation in the mind and body) as dominant constitution type. Conclusion: The study results demonstrated significant positive effects of yoga in diabetic individuals. This study has indicated the evidence for the safety and efficacy of the validated DYP for community-level interventions to prevent maladies like brain damage and stroke.